Reasons for delay in decision making and reaching health facility among obstetric fistula and pelvic organ prolapse patients in Gondar University Hospital, Northwest Ethiopia - Adefris, Mulat; Mekonnen, Solomon; Terefe, Kiros; Addis, Abebaw; Adigo, Azmeraw; Amare, Selamawit; Berhe, Aster; Lazaro, Dorothy; Baye, Chernet (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To assess reasons for the delay in getting treatment of women with obstetric fistula and pelvic organ prolapse at Gondar University Hospital. Methods: A hospital based cross-sectional study was conducted among 384 women. Delay was evaluated by calculating symptom onset and time of arrival to get treatment at University of Gondar Hospital. Regression analysis was conducted to elicit predictors of delay for treatment. Results: Of the total 384 participants 73(19.1%) were fistula cases and 311 (80.9%) were pelvic organ prolapse. The proportion of women who delayed for treatment of pelvic organ prolapse was 82.9%, and that of obstetric fistula was 60.9%. Women who had fear of disclosure due to social stigma (AOR=2; 1.03, 3.9), and financial problem (AOR=1.97; 1.01, 3.86) were associated with delay to seek treatment for pelvic organ prolapse. While increasing age (AOR =1.12; 1.01, 1.24)and divorce (AOR = 16.9; 1.75, 165.5) were associated with delay to seek treatment among obstetric fistula cases, Conclusions: A high proportion of women with pelvic organ prolapse and Obstetric fistula were delayed to seek treatment. Fear of disclosure due to social stigma and financial problem were the major factors that contributed for delay to seek treatment for pelvic organ prolapse. While increasing age and divorce were the predictors for delay to seek treatment for obstetrics fistula patients.